2012
DOI: 10.1246/cl.2012.162
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Synthesis and Charge–Discharge Properties of LiMnPO4 Nanocrystallite-embedded Porous Carbons

Abstract: LiMnPO 4 nanocrystallite-embedded porous carbons were successfully synthesized within a few minutes by a microwaveheating process. The nanocomposites showed higher charge discharge capacity and better rate capability than bulk-LiMnPO 4 particles synthesized in a similar manner without porous carbons.Olivine-type lithium metal phosphates have attracted much attention as a potential cathode material for secondary lithiumion batteries due to the relatively high theoretical capacity (ca. 170 mA h g ¹1 ) as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Used as a cathode, the product delivered a capacity of 168 mAh g −1 at 0.1 C and 105 mAh g −1 at 5 C. At 1 C, the initial capacity was 135 mAh g −1 with, however, a capacity retention of 81% at the 50th cycle [126]. These results were actually an improvement with respect to prior reports on C-LMP prepared by high-energy milling [127], solid-state reaction [128], microwave heating [129] (capacity of 140 mAh g −1 at 0.05 C), or even spray pyrolysis [130] or chemical vapor deposition [131] (147 mAh g −1 at 0.05 C in both cases). Since then, better rate capabilities have been obtained with almost spherical C-LMP particles of very small size (8-12 nm) by a solvothermal method using sucrose as the carbon precursor [132].…”
Section: Carbon Coatingmentioning
confidence: 59%
“…Used as a cathode, the product delivered a capacity of 168 mAh g −1 at 0.1 C and 105 mAh g −1 at 5 C. At 1 C, the initial capacity was 135 mAh g −1 with, however, a capacity retention of 81% at the 50th cycle [126]. These results were actually an improvement with respect to prior reports on C-LMP prepared by high-energy milling [127], solid-state reaction [128], microwave heating [129] (capacity of 140 mAh g −1 at 0.05 C), or even spray pyrolysis [130] or chemical vapor deposition [131] (147 mAh g −1 at 0.05 C in both cases). Since then, better rate capabilities have been obtained with almost spherical C-LMP particles of very small size (8-12 nm) by a solvothermal method using sucrose as the carbon precursor [132].…”
Section: Carbon Coatingmentioning
confidence: 59%
“…The underlying issues come from its inferior electronic conductivity (,10 210 S cm 21 ) and poor ionic conductivity (,10 216 -10 214 cm 2 s 21 ) 2 caused by the polaronic holes localized on the Mn 3+ sites and the strain at the MnPO 4 -LiMnPO 4 interface. [3][4] These issues could be addressed by reducing particle size to the nanoscale [5][6][7][8][9][10] and coating the surface with a carbon layer, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] both of which could be assembled as LiMnPO 4 -C nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…LiMnPO 4 -C powders with a specific capacity of 68 mA h g 21 at 0.05 C were obtained by highenergy milling. 22 A flower-like LiMnPO 4 -C composite prepared by a solid-state reaction showed a reversible capacity of 85 mA h g 21 at a rate of 0.05 C. 23 Aono et al synthesized a LiMnPO 4 -C nanocomposite by a microwave-heating process that showed a discharged capacity of 140 mA h g 21 at a rate of 0.05 C. 24 LiMnPO 4 -C nanocomposites prepared by spray pyrolysis followed by a heat treatment exhibited an initial discharge capacity of 147 mA h g 21 at 0.05 C. 25 The chemical vapor deposition (CVD) method was developed for LiMnPO 4 -C powders with a reversible capacity of 147 mA h g 21 at a rate of 0.05 C. 26 Later, the effect of different carbon sources on the electrochemical property of a LiMnPO 4 -C composite was also studied. 27 The differences of the composites in electrochemical performance were assigned to the graphitization degree of the carbon layer.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Enhanced chargedischarge properties were also reported on LiMn 2 O 4 , of which redox reactions are generally observed around 4 and 3 V vs. Li/Li + . 15 The latter redox is accompanied with rearrangement of atoms and large lattice volume change by the phase transition between cubic and tetragonal crystal phases; thus its capacity is very small for bulk LiMn 2 O 4 .…”
Section: Charge-discharge Properties Of Nanosized Materialsmentioning
confidence: 93%
“…Similar behavior was also observed on LiMnPO 4 -embedded nanoporous carbons. 13 A more suitable post modification should be coating with host nanolayer on the inner surface of porous carbons with appropriate pore size so as to provide nanopore channels for electrolyte transport. The possibility was demonstrated by a simulation, and actually prepared V 2 O 5 nanolayer-coating of CCT-derived porous carbons maintained a high charge discharge capacity up to extremely high current densities due to the rapid Li intercalation into whole V 2 O 5 nanophases.…”
Section: Nanoporous Materials As a Potential Lib Electrode Materialsmentioning
confidence: 99%